Efficacy of Three Denture Cleansers on Candida-Related Denture Stomatitis - Lamia T Rejab; Oday A Al-Abbod (University of Mosul, College of Dentistry, 2013)
Aim: The aim of the study is to evaluate the efficacy of three dentures cleanser on Candida related denture stomatitis through assessing their ability to reduce the number of colony forming unit (CFU) of Candida on palate of the patient for different times. Materials and methods: Group of 12 patients who have denture stomatitis were divided into four groups according to the type of denture cleaners (Protefix, sodium hypochlorite solution 0.02%, saturated sodium chloride salt solution and control wa-ter). The microbiological examination was done to determine the efficacy of the cleansers that used by assessing the number of (CFU) at different times (day before treatment and after 14, 28days of treat-ment). The data were statistically analyzed, (ANOVA) followed by Duncan's multiple Range test to assess the significant difference between the groups at P≤0.05. Results: The results showed that there was a significant effect of three cleansers on reducing number of (CFU) of Candida species in the treatment of denture stomatitis after 14 and 28 days of treatment, but it was not significant for control water group. Sodium hypochlorite showed the highest efficacy. Conclusions: Result showed that there was no significant difference in the efficacy between the three cleansers indicating that all cleansers are effective in the treatment of denture stomatitis .